Effects of residual carbon on microstructure and surface roughness of PIM 316L stainless steel - ., Muhammad Rafi Raza, Faiz Ahmad, Norhamidi Muhamad, Abu Bakar Sul (2015)
Powder injection molding (PIM) offers an attractive method for producing smart and intricate shapes components. PIM process is cost effective and equally applicable for metals and ceramics. Debinding process is the most critical step among all PIM steps and any residual during debinding can change the composition of sintered product resulting change in final properties. In this research work, the injection molded samples were thermally debound and sintered in various atmospheres. The results showed that the sintered samples with improper thermal debinding resulted the carbide formation at the surface and across the grain boundaries that caused to increase the roughness value.